2024
DOI: 10.1002/advs.202306253
|View full text |Cite
|
Sign up to set email alerts
|

A Frog Skin‐Derived Peptide Targeting SCD1 Exerts Radioprotective Effects Against Skin Injury by Inhibiting STING‐Mediated Inflammation

Fenghao Geng,
Li Zhong,
Tingyi Yang
et al.

Abstract: The extensive application of nuclear technology has increased the potential of uncontrolled radiation exposure to the public. Since skin is the largest organ, radiation‐induced skin injury remains a serious medical concern. Organisms evolutionally develop distinct strategies to protect against environment insults and the related research may bring novel insights into therapeutics development. Here, 26 increased peptides are identified in skin tissues of frogs (Pelophylax nigromaculatus) exposed to electron bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…And the UV-VIS and multi-omics in our recent research, has uncovered significant alterations in the activity of peptidases or endopeptidases within irradiated skin tissues. 17 In the current study, we examined the peptide profile after UVB radiation, in which skin tissues were grinded for sonication and the supernatants were applied to 10 kDa MWCO filters. The results showed an increased expression of small molecule gene-coding peptides (named UIFSPs) after intermittent UVB exposure, and peptide annotation revealed that UVB may act on structural proteins and induce UIFSPs production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And the UV-VIS and multi-omics in our recent research, has uncovered significant alterations in the activity of peptidases or endopeptidases within irradiated skin tissues. 17 In the current study, we examined the peptide profile after UVB radiation, in which skin tissues were grinded for sonication and the supernatants were applied to 10 kDa MWCO filters. The results showed an increased expression of small molecule gene-coding peptides (named UIFSPs) after intermittent UVB exposure, and peptide annotation revealed that UVB may act on structural proteins and induce UIFSPs production.…”
Section: Discussionmentioning
confidence: 99%
“…WS1 and HaCaT cells were seeded in a 96‐well plate at a density of 1 × 10 4 cells per well. 17 Then, cell viability was measured using the CCK‐8 according to the manufacturer's protocol, with a BioTek reader (Synergy HTX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation